AB0671 Increased body fat but decreased lean body mass and bone mineral density in patients with idiopathic inflammatory myopathies are associated with disease duration, inflammatory status, skeletal muscle involvement and physical activity. (15th June 2017) - Oreska, S; Spiritovic, M; Cesak, P; Marecek, O; Storkanova, H; Kubinova, K; Klein, M; Vernerova, L; Ruzickova, O; Becvar, R; Pavelka, K; Senolt, L; et al.
Abstract : Background: Idiopathic inflammatory myopathies (IIM) are characterized by inflammation and atrophy of skeletal muscles, pulmonary and articular involvement, which limit the mobility/self-sufficiency of patients, and can have a negative impact on body composition. Objectives: To assess body composition and physical activity of IIM patients and healthy controls (HC). Methods: 54 patients with IIM (45 females/9 males; mean age 57.3; disease duration 5.8 years; polymyositis (PM, 22)/dermatomyositis (DM, 25)/necrotizing myopathy (IMNM, 7)) and 30 age-/sex-matched HC (25 females/5 males, mean age 54.9) without rheumatic/tumor diseases or manifest cardiovascular event were included. PM/DM patients fulfilled Bohan/Peter criteria for PM/DM. Anthropometric parameters and body composition were assessed (by densitometry-iDXA Lunar, and by bioelectric impedance-BIA2000-M), and physical activity was evaluated using Human Activity Profile (HAP) questionnaire. Routine biochemistry analysis was performed after 8 hours of fasting. Muscle involvement was evaluated by manual muscle test (MMT)-8. Data are presented as mean±SD. Results: Compared to HC, patients with IIM had significantly increased body fat % as assessed by iDXA (BF%: 38.7±6.7 vs. 42.5±7.1%, p=0.015), but decreased lean body mass as assessed both by iDXA (LBM: 45.7±6.6 vs. 40.3±7.0 kg, p=0.0005) and BIA (LBM: 53.2±8.5 vs. 48.7±9.0 kg, p=0.0295), and increased ECM/BCM ratio (extracellular mass/body cell mass: 1.00±0.12 vs. 1.43±0.42, p<0.0001), which reflects worse muscle predispositions for physical exercise, aerobic fitness/performance, and also increases with deteriorating nutritional status. Compared to HC, IIM patients had significantly lower bone mineral density (BMD: 1.16±0.10 vs. 1.05±0.11 g/cm 2, p=0.0010), and were currently able to perform less energetically demanding physical activities according to HAP score (86.3±5.9 vs. 49.0±20.2, p<0.0001). Disease duration negatively correlated with BMD (r=-0.392, p=0.004) and LBM-BIA (r=-0.272, p=0.047). CRP was positively associated with BF% assessed both by DEXA (r=0.276, p=0.035) and BIA (r=0.306, p=0.025). MMT-8 score negatively correlated with ECM/BCM ratio (r=-0.385, p=0.006), and physical activity (HAP) negatively correlated with BF%>DEXA (r=-0.292, p=0.032). Conclusions: Compared to healthy age-/sex-matched individuals we found significant negative changes in body composition of our IIM patients, which are associated with their disease duration, inflammatory status, skeletal muscle involvement, and physical activity, and could reflect their impaired nutritional status and predispositions for physical exercise, aerobic fitness and performance. Acknowledgements: Supported by AZV-16–33574A, GAUK-214615. Disclosure of Interest: None declared